2011
DOI: 10.1308/003588411x564005
|View full text |Cite
|
Sign up to set email alerts
|

Ankle arthroscopy in children

Abstract: INTRODUCTION Arthroscopy of the ankle has gained acceptance as a procedure for diagnosing and treating chronic and post-traumatic ankle problems. The senior author's perception is that magnetic resonance imaging (MRI) under-diagnoses anterior soft tissue impingement lesions in children. The purpose of this study was retrospectively to analyse the outcome of ankle arthroscopy in the paediatric age group. PATIENTS AND METHODS Between March 2005 and September 2007, 23 children underwent ankle arthroscopy for post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…MRI is considered a useful diagnostic modality for assessment of the pathology in ankle impingement[6,14]. However, MRI has been shown to be an insensitive modality for ankle imaging in the pediatric population[15]. The most common MRI findings in our study included the presence of an os trigonum or Stieda process, with associated osseous and soft tissue edema which is similar to what prior studies in the literature have reported[6,12,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is considered a useful diagnostic modality for assessment of the pathology in ankle impingement[6,14]. However, MRI has been shown to be an insensitive modality for ankle imaging in the pediatric population[15]. The most common MRI findings in our study included the presence of an os trigonum or Stieda process, with associated osseous and soft tissue edema which is similar to what prior studies in the literature have reported[6,12,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ankle arthroscopy in the management of chronic and post-traumatic ankle disorders in adults is well established. Uglow and colleagues [11] reported outcomes in children following arthroscopy being comparable to adult series for the management of OCDs and anterolateral soft tissue impingement. In particular they highlighted the poor correlation between findings on MRI and intraoperative findings on arthroscopy especially in relation to small OCDs and impingements lesions.…”
Section: A B D Cmentioning
confidence: 92%
“…[12][13][14] Sin embargo, existe mínima información sobre la eficacia y seguridad de este procedimiento aplicado a patologías del tobillo en niños y adolescentes. [15][16][17][18] El objetivo de este estudio es revisar las indicaciones y complicaciones de la artroscopia de tobillo en una cohorte de pacientes ≤ 18 años. Debido a que el tamaño de la articulación en niños es menor (lo que incrementa la dificultad técnica) y el volumen de cirugías en el mismo periodo también es menor (lo que alarga la curva de aprendizaje), nuestra hipótesis es que el porcentaje de complicaciones sería mayor.…”
Section: Introductionunclassified